Pemanfaatan Ekstrak Kunyit (Curcuma domestica Val.) sebagai Pewarna Alami Pembuatan Preparat Awetan Jaringan Tumbuhan dalam Praktikum Biologi Sel - Asmi Ode; Sriyati Sampulawa; Fauzia Hulopi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Making preparations for observing cells or tissues in practicum activities requires dyes. In cell biology practicum, especially observation of plant tissue in the Department of Biology Education, FKIP, Ambon University of Darussalam, it is still very limited, because it does not have chemical dyes for making preserved preparations. This is because chemical dyes are quite expensive, unsafe, and will spoil if stored for a long time, so it is very important to make natural dyes as a substitute for synthetic dyes so that the preserved preparations produced are safer, more affordable, and can be used for a long time. which is old. Sources of natural dyes are obtained from plant parts, for example: roots, bark, leaves, fruit, wood, seeds, and flowers. Turmeric (Curcuma domestica Val.) is a natural dye that can be used, because it is relatively cheap, easy to find, non-carcinogenic, and biodegradable. The active pigments in turmeric which can color plant tissue and give it a yellow color are curcuminoids. The aim of this research was to study the utilization of turmeric extract (Curcuma domestica Val.) as a natural dye for preparing preserved preparations of plant tissues in cell biology practicum. This type of research is experimental research, which has several stages of research including: observation, preparation, research implementation, and analysis stage. At the data analysis stage, a qualitative descriptive method was used to determine the quality of the preserved preparations. The quality of the preparations in this study was expressed by the percentage of eligibility of ≥ 62.5% or feasible criteria. The results showed that the average percentage of the quality of the preparations that had been validated was 66.96% and 67.85% with proper criteria. This shows that the preserved preparations made are suitable for observing plant tissues in cell biology labs.